2019
DOI: 10.1016/j.atmosenv.2019.116824
|View full text |Cite
|
Sign up to set email alerts
|

Retrieval of optical and microphysical properties of transported Saharan dust over Athens and Granada based on multi-wavelength Raman lidar measurements: Study of the mixing processes

Abstract: In this paper we extract the aerosol microphysical properties for a collection of mineral dust cases measured by multi-wavelength depolarization Raman lidar systems located at the National Technical University of Athens (NTUA, Athens, Greece) and the Andalusian Institute for Earth System Research (IISTA-CEAMA, Granada, Spain). The lidar-based retrievals were carried out with the Spheroidal Inversion eXperiments software tool (SphInX) developed at the University of Potsdam (Germany). The software uses regulariz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
19
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(24 citation statements)
references
References 93 publications
3
19
0
Order By: Relevance
“…Studies based on CALIPSO data obtained over the mid and high latitudes, showed that BB plumes can be equally injected within the mixing layer (50%) and the free troposphere (50%) [ 13 , 16 ]. On the other hand, the LPDR values ( Figure 9 c) for the smoke mixtures with dust ranged from 0.10 ± 0.05 to 0.20 ± 0.04, in all subregions, which is in accordance with values previously found in the literature [ 19 , 21 , 37 , 38 , 39 ]. The relevant values for the pure smoke aerosols were found equal to 0.05 ± 0.04, again in agreement with literature findings [ 7 , 17 , 40 ].…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…Studies based on CALIPSO data obtained over the mid and high latitudes, showed that BB plumes can be equally injected within the mixing layer (50%) and the free troposphere (50%) [ 13 , 16 ]. On the other hand, the LPDR values ( Figure 9 c) for the smoke mixtures with dust ranged from 0.10 ± 0.05 to 0.20 ± 0.04, in all subregions, which is in accordance with values previously found in the literature [ 19 , 21 , 37 , 38 , 39 ]. The relevant values for the pure smoke aerosols were found equal to 0.05 ± 0.04, again in agreement with literature findings [ 7 , 17 , 40 ].…”
Section: Resultssupporting
confidence: 90%
“…In R2, the AΕ mean values were found equal to 0.6 for smoke mixed with marine aerosol layers, and to 1.6 ± 0.1 for smoke mixed with dust aerosols. In R3 and R4 subregions, the values of AΕ ranged from 0.7 to 1.5 and 0.9 to 1.2, respectively, again in agreement with values found in the literature for pure smoke and smoke mixtures [ 22 , 38 , 40 , 41 ].…”
Section: Resultssupporting
confidence: 89%
“…The back-trajectories ( Figure 7) show that the air masses present over Transylvania-Cluj-Napoca station on April the 24th 2019 during the lidar measurements originated from the Saharan desert. Similar to the [60] study, we can analyze the air masses dynamics using Figure 7. For the trajectories that were obtained for a period of 72 hours backward in time, the traveling time from the African continent to the detection station (after leaving the African continent) is less than 48 hours, which comes in support of the previous assumption that the dust plume is relatively pure.…”
Section: Modelling Data Analysismentioning
confidence: 99%
“…The analysis of 5 d backward trajectories (Fig. 1) computed by the HYSPLIT model (Hybrid Single-Particle Lagrangian Integrated Trajectory; Stein et al, 2015;Rolph, 2016) indicate that the air masses that arrived at Granada came from a south-western direction on 18 and 21 July 2016. These air masses from the Sahara area passed along south Morocco and the Moroccan coast before reaching Granada.…”
Section: Dust Event During Slope I Campaignmentioning
confidence: 99%